2008
DOI: 10.5194/acp-8-1311-2008
|View full text |Cite
|
Sign up to set email alerts
|

Modelling sea salt aerosol and its direct and indirect effects on climate

Abstract: Abstract.A size-dependent sea salt aerosol parameterization was developed based on the piecewise log-normal approximation (PLA) for aerosol size distributions. Results of this parameterization from simulations with a global climate model produce good agreement with observations at the surface and for vertically-integrated volume size distributions. The global and annual mean of the sea salt burden is 10.1 mg m −2 . The direct radiative forcing is calculated to be −1.52 and −0.60 W m −2 for clear sky and all sk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 73 publications
6
88
0
Order By: Relevance
“…The aerosol particles have a substantial impact on the radiative balance of the Earth through scattering of incident solar radiation and as a source of cloud condensation nuclei (CCN). Different model estimates of the global annual mean clear sky direct radiative forcing due to sea salt range between −0.6 W m −2 and −5.03 W m −2 (compilation of results in Ma et al, 2008). Clarke et al (2006) reported that sea salt aerosols may account for between 5 % and 90 % of the CCN in the marine atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The aerosol particles have a substantial impact on the radiative balance of the Earth through scattering of incident solar radiation and as a source of cloud condensation nuclei (CCN). Different model estimates of the global annual mean clear sky direct radiative forcing due to sea salt range between −0.6 W m −2 and −5.03 W m −2 (compilation of results in Ma et al, 2008). Clarke et al (2006) reported that sea salt aerosols may account for between 5 % and 90 % of the CCN in the marine atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the idea is to spray naturally occurring sea salt particles into low-lying stratiform clouds over the tropical oceans to increase the available cloud condensation nuclei, thus increasing the concentration of smaller cloud droplets and the reflectivity of the clouds (Latham, 1990). The sea salt aerosols are reflective themselves (e.g., Ma et al, 2008), adding to the cooling potential of the method. Cirrus cloud thinning (CCT) on the other hand, aims to increase the amount of outgoing longwave radiation at the top of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Water retention in snowpacks has also been incorporated. CanAM4.2 also includes an aerosol microphysics scheme (von Salzen, 2006;Ma et al, 2008;Peng et al, 2012), a higher vertical resolution in the upper troposphere, a reduced solar constant (1361 W m −2 ) and an improved treatment of the solar continuum used in the radiative transfer. CanAM4.2 also considers natural and anthropogenic aerosols and their emissions, transport, gas-phase and aqueous-phase chemistry, and dry and wet deposition as summarized in Namazi et al (2015) …”
Section: The Coupled Climate-carbon Systemmentioning
confidence: 99%